Efficacy of self-management exercise program with spa therapy for behavioral management of knee osteoarthritis: research protocol for a quasi-randomized controlled trial (GEET one) - Chloe Gay; Candy Guiguet-Auclair; Bruno Pereira; Anna Goldstein; Loïc Bareyre; Nicolas Coste; Emmanuel Coudeyre (BMC, 2018)
Abstract Background Osteoarthritis (OA) is not limited to joint pain and stiffness, which can lead to disability; it is also linked to comorbidities such as overweight, obesity and fears and beliefs related to the pathology. The knee OA population appears more affected by these risk factors and has a lower physical activity (PA) level than the general population. The key challenge for OA treatment is increasing the PA level to decrease the risk factors. Methods We aim to perform a prospective, multicentric, quasi-randomized controlled trial with an alternate-month design (1-month periods). People aged 50-75 years old with symptomatic knee OA (stage I-IV Kellgren and Lawrence scale) with low and moderate PA level will be included in 3 spa therapy resorts. The experimental arm will receive 5 self-management exercise sessions (1.5 h each; education, aerobics, strength training, range of motion) + an information booklet + 18 sessions (1 h each) of spa therapy treatment (STT). The active comparator arm will receive an information booklet + 18 sessions of STT. The primary outcome will be a change at 3 months in PA level (International Physical Activity Questionnaire short form score). Secondary outcomes will be function (WOMAC) pain (numerical scale), anxiety/depression (HAD), fears and beliefs about OA (KOFBeQ) and arthritis self-efficacy (ASES). The barriers to and facilitators of regular PA practice will be assessed by using specific items specifically designed for the study because of lack of any reference scale. Discussion The study could demonstrate the impact of a self-management exercise program associated with spa therapy in the medium term by increasing PA level in people with OA. A benefit for ameliorating fears and beliefs and anxiety/depression and improving self-efficacy will also be analysed. The findings could offer new prospects while establishing best clinical practice guidelines for this population. Trial registration ClinicalTrials.gov NCT02598804 (November 5, 2015).